Left ventricular unloading with Impella versus IABP in patients on VA-ECMO for cardiogenic shock. (3rd October 2022) - Aggarwal, D; Bhatia, K; Lopez, P; Bohra, C; Joshi, A; Daibes, J; Mahmood, K; Fox, A
Abstract: Background: Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) use for circulatory support in shock is limited by increased left ventricular afterload. Impella and intra-aortic balloon pump (IABP) can be used in conjunction with VA-ECMO to help unload the left ventricle. Data comparing the two strategies are limited. Purpose: We performed a systematic review and meta-analysis of published data to compare outcomes of patients with shock supported by VA-ECMO in conjunction with Impella versus IABP. Methods: We conducted a search of Medline, Embase, and Cochrane databases to identify studies comparing the use of Impella versus IABP in patients on VA-ECMO. The primary outcome of interest was all-cause mortality (in-hospital or 30-day). Secondary outcomes included transition to destination therapy with left ventricular assist device (LVAD) or transplant, stroke, need for continuous renal replacement therapy (CRRT), bleeding, and hemolysis. Risk ratios (RR) with 95% confidence interval and the heterogeneity statistic I 2 were reported for each outcome. Results: Six observational studies with a total of 629 patients were included in the analysis. Of these, 205 (33%) and 424 (67%) patients were supported by Impella and IABP respectively, in addition to VA-ECMO. All six studies reported the primary outcome. No difference was observed in all-cause mortality between VA-ECMO with Impella and VA-ECMO with IABP (RR 1.02 [0.74–1.40], I 2 =74%). Similar rates were observed for transition to LVAD or transplant (RR 0.75 [0.45–1.27], I 2 =0%), stroke (RR 1.50 [0.80–2.83], I 2 =0%), and need for CRRT (RR 1.04 [0.82–1.32], I 2 =0%). However, use of VA-ECMO with Impella was associated with a higher risk of bleeding (RR 1.91 [1.28–2.86], I 2 =68%) and hemolysis (RR 4.61 [1.24–17.17], I 2 =66%) as compared with use of VA-ECMO with IABP. Conclusion: In patients with shock requiring VA-ECMO, concurrent use of Impella and IABP had similar risk of mortality, transition to LVAD/transplant, stroke, and need for CRRT. However, Impella use was associated with higher risk of bleeding and hemolysis. Randomized trials are needed to identify the optimal strategy for left ventricular unloading in patients with cardiogenic shock on VA-ECMO. Funding Acknowledgement: Type of funding sources: None.